Question:

If \( \vec{f} = i + j + k \) and \( \vec{g} = 2i - j + 3k \), then the projection vector of \( \vec{f} \) on \( \vec{g} \) is:

Show Hint

The projection formula \( \text{Proj}_{\vec{g}} (\vec{f}) = \frac{\vec{f} \cdot \vec{g}}{|\vec{g}|^2} \vec{g} \) is useful in many vector calculations, including physics and engineering.
Updated On: Mar 25, 2025
  • \( \frac{2}{7} (i + j + k) \)
  • \( \frac{2}{7} (2i - j + 3k) \)
  • \( \frac{1}{3} (i + j + k) \)
  • \( \frac{1}{14} (2i - j + 3k) \)
Hide Solution
collegedunia
Verified By Collegedunia

The Correct Option is B

Solution and Explanation

We are given two vectors: \[ \vec{f} = \hat{i} + \hat{j} + \hat{k}, \quad \vec{g} = 2\hat{i} - \hat{j} + 3\hat{k} \] Step 1: Recall the Formula for Projection The projection vector of \( \vec{f} \) on \( \vec{g} \) is given by: \[ \text{Proj}_{\vec{g}} \vec{f} = \frac{\vec{f} \cdot \vec{g}}{|\vec{g}|^2} \vec{g} \] Step 2: Compute the Dot Product \[ \vec{f} \cdot \vec{g} = (1)(2) + (1)(-1) + (1)(3) \] \[ \vec{f} \cdot \vec{g} = 2 - 1 + 3 = 4 \] Step 3: Compute \( |\vec{g}|^2 \) \[ |\vec{g}|^2 = (2)^2 + (-1)^2 + (3)^2 \] \[ |\vec{g}|^2 = 4 + 1 + 9 = 14 \] Step 4: Compute the Projection Vector \[ \text{Proj}_{\vec{g}} \vec{f} = \frac{4}{14} \vec{g} = \frac{2}{7} \vec{g} \] \[ = \frac{2}{7} (2\hat{i} - \hat{j} + 3\hat{k}) \] Step 5: Final Answer 

\[Correct Answer: (2) \ \frac{2}{7} (2\hat{i} - \hat{j} + 3\hat{k})\]
Was this answer helpful?
0
0

Top Questions on Vectors

View More Questions